Strategic Human Resource Development And Digital Leadership Toward Employee Performance In Smart Organizations - Muh. Anugrah Prabowo Putra; Fitriani; Achmad Ridha (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study investigates the influence of Strategic Human Resource Development (SHRD) and Digital Leadership (DL) on Employee Performance (EP) within the context of smart organizations in Makassar City, Indonesia. The study responds to the accelerating digital transformation that requires organizations to strengthen both human capital strategies and leadership competencies. Using a quantitative explanatory design, data were collected from 150 employees and line managers across financial services, digital marketing, and telecommunication sectors through a structured questionnaire using a seven-point Likert scale. The data were analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The measurement model showed satisfactory reliability and validity (CR > 0.80; AVE > 0.50), while the structural model revealed that both SHRD (β = 0.61; p < 0.001) and DL (β = 0.21; p < 0.01) significantly influence employee performance, explaining 58.2% of its variance (R² = 0.582). These results indicate that strategic HRD serves as a stronger and more direct predictor of performance, while digital leadership functions as a contextual enabler fostering innovation and adaptability. Theoretically, the study extends the Resource-Based View and Dynamic Capability Theory, demonstrating that performance in smart organizations is achieved through the synergy between structured human development and visionary leadership. Practically, it emphasizes that sustainable digital transformation in emerging economies must begin with strategic human transformation. Future research should explore mediating variables such as engagement or digital culture to enrich the conceptual framework of digital HRD.